Corrupção corporativa e conexões políticas: relações e efeitos no desempenho econômico das empresas e dos países. - Cavalcante, Danival Sousa (2021)
Corruption is one of the biggest challenges faced in the 21st century (OECD, 2016), associated with political-organizational connections, it can cause different effects for organizations and nations. The objective of this research, which is based on the Resource Dependence Theory, is to investigate the effects of corporate corruption and political connections on the economic performance of companies, considering the time surrounding the practice of corruption, and the host countries of the convicted companies. To achieve this, the study sample consists of 131 companies listed on the NYSE and NASDAQ, which were convicted of corrupt practices by the Securities and Exchange Commission (SEC) for violating the US Foreign Corrupt Practices Act (FCPA) between 1987 and 2019, and a control group was used, by Propensity Score Matching (PSM) technique, formed with same number of companies in the sample, but not convicted of corruption. It was concerned with analyzing the effects on the economic performance of companies at times around corruption, before, during and after the corruptive practice, considering two sources of information: the SEC, as official source, based on the disclosure of the company's conviction; and newspapers and specialized media and other news sources (JME and others) as unofficial source, based on early release of news about corruption cases. At the country level, data from 18 host countries of the companies sampled were analyzed, with a concentration already expected by companies in the United States. Descriptive statistical techniques, correlation analysis, mean comparison tests (t test and analysis of variance) and multiple regression analysis were applied to the data. The main finding of the study does not confirm the thesis defended, as it is found that the economic performance of companies convicted of corruption manifested itself in a continuous growing movement over time around the practice, having presented superior performance in the moment after the practice was discovered, both in the year in which the company was convicted, and in the year in which news was previously disclosed to the market. There was an increase in the performance of companies even after the practice was discovered and disclosed to the market, and this increase was not higher only while the practice of corruption was hidden. At the country level, there was no explanatory power of the practice of corporate corruption for this effect on the economic performance of countries, and it cannot be ensured that the corruption practiced by companies interferes in the economic performance of the countries where they are headquartered. These findings cannot be generalized, they refer to data from a small number of companies and countries, objects of a non-probabilistic sample. However, such findings can be relevant and useful for organizations, for the State/Government and for stakeholders in general for making strategic decisions, investments and policies that refer to controlling corruption and maintaining alliances policies.